Be Divergent, Be Green! The Moderating Role of Gender in the Association Between Divergent Thinking and Pro-Environmental Behaviours in Children - Marta Sannino; Elisa Galli; Cristina Zacheo; Marco Giancola (Children)
Background/Objectives: The environmental crisis has begun as a daily challenge for present and forthcoming generations. This scenario highlights the need to adopt many pro-environmental strategies to avoid its adverse consequences. Consequently, it is of paramount importance to comprehend the fundamental psychological and cognitive characteristics that may encourage young children to participate in Pro-Environmental Behaviours (PEBs). Previous research has explored key psychological factors like values, norms, and beliefs influencing children’s pro-environmental behaviours (PEBs), but the impact of cognitive processes is still debated. This research explored the association between divergent thinking (DT) and PEBs, also addressing the potential involvement of gender. Methods: The study involved 348 children (Mage = 8.78 years; SDage = 1.79; range age 6–13; 174 girls) who completed a socio-demographic questionnaire, the Pro-Environmental Behaviour Questionnaire, and the Alternative Uses Task (AUT). Results: The statistical analysis indicated that gender moderates the relationship between children’s DT-creativity and PEBs (B = 0.08, SE = 0.04, t = 2.05; 95% CIs [0.0033, 0.1659]), strengthening this association. Conclusions: These findings yielded further evidence on the impact of cognitive processes, such as DT on PEBs, extending the knowledge regarding the critical role of gender in this intricate relationship.